A Low‐Dimensional Function Space for Efficient Spectral Upsampling. (7th June 2019) - Jakob, Wenzel; Hanika, Johannes
Abstract: We present a versatile technique to convert textures with tristimulus colors into the spectral domain, allowing such content to be used in modern rendering systems. Our method is based on the observation that suitable reflectance spectra can be represented using a low‐dimensional parametric model that is intrinsically smooth and energy‐conserving, which leads to significant simplifications compared to prior work. The resulting spectral textures are compact and efficient: storage requirements are identical to standard RGB textures, and as few as six floating point instructions are required to evaluate them at any wavelength. Our model is the first spectral upsampling method to achieve zero error on the full sRGB gamut. The technique also supports large‐gamut color spaces, and can be vectorized effectively for use in rendering systems that handle many wavelengths at once.